Pengaruh Green Product terhadap Purchase Decision dengan Brand Image dan Perceived Value sebagai Variabel Mediasi - Adellia Permana Sari; Asep Supriadi; Hayati Nufus (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study intends to analyze the impact of Green Product Purchase Decision, by considering the role of Brand Image and Perceived Value as mediating variables, which are studied on consumers of Ades branded bottled mineral water products in Tangerang Regency. This study applies a quantitative approach, with instruments in collecting data carried out through the distribution of questionnaires and searching for related literature. The population studied was Ades AMDK consumers living in Tangerang Regency, with 160 respondents selected as samples determined through the use of purposive sampling and accidental sampling techniques. The data processing process applied in this study was through the Structural Equation Modeling (SEM) approach strategy, which was operated through SmartPLS software version 4.0 Professional. The research findings prove that Green Products have a positive impact on Purchase Decision, both in the form of direct relationships and through the intermediary role of Brand Image and Perceived Value. The implication of this study is that companies need to strengthen environmentally friendly attributes and build a positive brand image to improve consumer behavior in making purchasing decisions.